Factores determinantes que contribuyen a la decisión de compra online en los jóvenes universitarios trujillanos año 2017 - Cueva Castillo, Joana Elizabeth (2018)
The present investigation has been elaborated with the purpose of establishing the determining factors that contribute in the decision of purchase online in the university young people trujillanos during the 2017. The problem formulated for the investigation was: Which are the determining factors that contribute in the decision of online shopping in the young university students Trujillanos year 2017?. And it was hypothesized: The determining factors that contribute to the online purchase decision are the prestige of a web page, the satisfaction of the online shopping process and the credibility of the website. The population subject to study was made up of Trujillo university students between the ages of 16 and 29 years old, enrolled in the 2017 semester II. The design of the research used was explanatory of cross-section, the methods that have been applied were: inductive-deductive method, analytical-synthetic method and statistical method; and as a research technique, a survey was applied to university students who had an online shopping experience. After this investigation we can conclude that there is enough evidence to show that the determining factors that contribute to the decision to purchase online in young university students Trujillanos, 2017 are prestige with 43%, followed by satisfaction with 33% and a 24% the credibility with which the hypothesis is demonstrated is for that reason that the virtual stores must take into account these determining factors at the time of elaborating their strategies and thus have the expected success.